Progressive upgrade processes for the energy retrofit of school buildings in Naples - Emilia Alborelli; Valeria D’Ambrosio (Techne, 2015)
In the last years, the progressive upgrade of buildings has significantly developed in many countries such as the USA  and the UK, following a planned approach based on the progressive implementation of retrofitting  works, in order to achieve effective and controlled targets of energy performance. This is the field of the research that the DiARC - Department of Architecture, University of Naples Federico II - has carried out along with Naples City Administration to develop a study activity and a decision making support tool for the energy requalification of school buildings, in cooperation with other subjects and operational Authorities on the territory. This paper reports the results of the first research phase, whose purpose was the definition of an operational methodology to identify scenarios for the progressive update of school buildings in Naples. Scenarios have been elaborated by means of a multi criteria analysis based on the parameters of environmental and economic sustainability and technical feasibility.